‘NOWT TO DO AND ALWAYS GETTING INTO TROUBLE’ The Bullwell Neighbourhood Project: A Social Action Response - Badham, Bill; Bente, Michael; Hall, Pauline (Groupwork)
This paper describes am inter-disciplinary response to young people at risk of offending* and having difficulties, whether at school, home or with the law. The work undertaken involved Social Services, the Youth Service, Probation and two voluntary sector protects’. The young people concerned belonged to two neighbourhoods in the Bulwell area of the City of Nottingham. The work started in the summer of 1984 and ended in the spring of1988. The article discusses: i the background to the neighbourhood work: its origins, the proposal, and social action principles; ii the neighbourhood work undertaken: working with young people, their issues and concerns, and action taken; ii. implications for agency practice: inter-agency meetings and consequences. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.